INITIATING IN THE PROCESS OF LEARNING TO READ NOTE FROM THE SHEET (Pedagogy of Higher and Secondary Education, 2002)
This article investigates the role and importance of imitation in the process of rea-ding musical notation as a specific psychological process with definite mechanisms and stages of its development. The results of the author's observation, as well as the teacher's role in the process of reading musical notation, are reported.
Keywords: 1